2013
DOI: 10.1007/s12160-012-9440-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bike Lane Infrastructure Improvements on Ridership in One New Orleans Neighborhood

Abstract: Background Incorporating cycling into daily life is one way to increase physical activity. Purpose This study examined the impact of building new bike lanes in New Orleans to determine whether more people were cycling on the street and with the flow of traffic after bike lanes were built. Methods Through direct observation of one intervention and two adjacent streets, observers counted cyclists riding on the street and sidewalk, with and against traffic, before and after installation of the lanes. Data were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 19 publications
1
69
1
Order By: Relevance
“…Fifteen primary studies (Boarnet et al, 2005a(Boarnet et al, , 2005bBuliung et al, 2011;Deehr and Shumann, 2009;Fitzhugh et al, 2010;Garrard and Crawford, 2010;Hinckson and Badland, 2011;Mammen et al, 2014aMammen et al, , 2014bMcDonald et al, 2013;Morrison et al, 2004;Moudon and Stewart, 2012;Parker et al, 2013;Wen et al, 2008) in relation to 12 interventions were identified which aimed to increase the level of active travel amongst children and young people.…”
Section: Active Travelmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen primary studies (Boarnet et al, 2005a(Boarnet et al, , 2005bBuliung et al, 2011;Deehr and Shumann, 2009;Fitzhugh et al, 2010;Garrard and Crawford, 2010;Hinckson and Badland, 2011;Mammen et al, 2014aMammen et al, , 2014bMcDonald et al, 2013;Morrison et al, 2004;Moudon and Stewart, 2012;Parker et al, 2013;Wen et al, 2008) in relation to 12 interventions were identified which aimed to increase the level of active travel amongst children and young people.…”
Section: Active Travelmentioning
confidence: 99%
“…Primary studies in relation to single component interventions included the addition of a bike lane in an urban area (Parker et al, 2013), retrofitting an urban greenway/ trail (Fitzhugh et al, 2010), and introduction of a traffic calming scheme (Morrison et al, 2004).…”
Section: Active Travelmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other studies evaluated the traffic operation and the level of service on the streets with bike lanes [11,12,[22][23][24]. In recent years, the interactions between bicycle and vehicle traffic flow on streets have gained much attention from transportation professionals [25][26][27][28][29]. However, those previous studies did not aim to evaluate and predict the vehicle delay caused by bicycles under different traffic situations which is still a critical issue that has not been addressed properly.…”
Section: Introductionmentioning
confidence: 99%